When Markets Talk: Volatility Spillovers Between the UK and China - Sadhwani, Ranjeeta; Ali, Rajib; Ghumro, Niaz Hussain; Khan, Shabeer (ETIKONOMI, 2026)
Research Originality: This study uniquely examines spillover effects among stock returns, gold prices, and exchange rates within the UK and China, as well as between them. Research Objectives: This study aims to examine volatility spillover effects among stock, gold, and exchange rate returns within and across the UK and China. Research Method: This study exploits monthly data from January 2000 to December 2024 and employs a bivariate GARCH model to analyze cross-market and cross-border volatility spillovers. Empirical Results:  The results demonstrate significant ARCH and GARCH effects, necessitating persistent volatility in markets to be studied. No evidence of mean spillover is observed in UK markets. However, volatility spillover persists from the exchange rate to gold within the UK and China. Cross-country analysis reveals one-way mean spillover from the UK to the Chinese equity market and bidirectional volatility spillovers in exchange rates and gold. Implications: For investors and portfolio managers, deciphering volatility spillover improves diversification strategies and helps to mitigate systemic risk. JEL Classification: C32, G11, G15